Assessing seizure burden in pediatric epilepsy using an electronic medical record–based tool through a common data element approach. (2nd June 2021) - Fitzgerald, Mark P.; Kaufman, Michael C.; Massey, Shavonne L.; Fridinger, Sara; Prelack, Marisa; Ellis, Colin; Ortiz‐Gonzalez, Xilma; Fried, Lawrence E.; DiGiovine, Marissa P.; ,; Melamed, Susan; Malcolm, Marissa; et al.
Abstract: Objective: Improvement in epilepsy care requires standardized methods to assess disease severity. We report the results of implementing common data elements (CDEs) to document epilepsy history data in the electronic medical record (EMR) after 12 months of clinical use in outpatient encounters. Methods: Data regarding seizure frequency were collected during routine clinical encounters using a CDE‐based form within our EMR. We extracted CDE data from the EMR and developed measurements for seizure severity and seizure improvement scores. Seizure burden and improvement was evaluated by patient demographic and encounter variables for in‐person and telemedicine encounters. Results: We assessed a total of 1696 encounters in 1038 individuals with childhood epilepsies between September 6, 2019 and September 11, 2020 contributed by 32 distinct providers. Childhood absence epilepsy ( n = 121), Lennox‐Gastaut syndrome ( n = 86), and Dravet syndrome ( n = 42) were the most common epilepsy syndromes. Overall, 43% (737/1696) of individuals had at least monthly seizures, 17% (296/1696) had a least daily seizures, and 18% (311/1696) were seizure‐free for >12 months. Quantification of absolute seizure burden and changes in seizure burden over time differed between epilepsy syndromes, including high and persistent seizure burden in patients with Lennox‐Gastaut syndrome. Individuals seen via telemedicine or in‐person encounters had comparable seizure frequencies. Individuals identifying as Hispanic/Latino, particularly from postal codes with lower median household incomes, were more likely to have ongoing seizures that worsened over time. Significance: Standardized documentation of clinical data in childhood epilepsies through CDE can be implemented in routine clinical care at scale and enables assessment of disease burden, including characterization of seizure burden over time. Our data provide insights into heterogeneous patterns of seizure control in common pediatric epilepsy syndromes and will inform future initiatives focusing on patient‐centered outcomes in childhood epilepsies, including the impact of telemedicine and health care disparities.